Electronic Properties of Defective MoS\(_{2}\) Monolayers Subject to Mechanical Deformations: A First-Principles Approach - Bahmani, Mohammad; Faghihnasiri, Mahdi; Lorke, Michael; Agnieszka-Beata Kuc; Frauenheim, Thomas (arXiv.org, 2019)
Monolayers (ML) of Group-6 transition-metal dichalcogenides (TMDs) are semiconducting two-dimensional materials with direct bandgap, showing promising applications in various fields of science and technology, such as nanoelectronics and optoelectronics. These monolayers can undergo strong elastic deformations, up to about 10%, without any bond breaking. Moreover, the electronic structure and transport properties, which define the performance of these TMDs monolayers in nanoelectronic devices, can be strongly affected by the presence of point defects, which are often present in the synthetic samples. Thus, it is important to understand both effects on the electronic properties of such monolayers. In this work, we have investigated the electronic structure and energetic properties of defective MoS\(_{2}\) monolayers, as subject to various strains, using density functional theory simulations. Our results indicated that strain leads to strong modifications of the defect levels inside the bandgap and their orbital characteristics. Strain also splits the degenerate defect levels up to an amount of 450~meV, proposing novel applications.